2011
DOI: 10.1126/scitranslmed.3003130
|View full text |Cite
|
Sign up to set email alerts
|

The PDL1-PD1 Axis Converts Human T H 1 Cells into Regulatory T Cells

Abstract: Immune surveillance by T helper type 1 (Th1) cells is critical for the host response to tumors and infection, but also contributes to autoimmunity and graft-versus-host disease (GvHD) after transplantation. The inhibitory molecule programmed death ligand-1 (PDL1) has been shown to anergize human Th1 cells, but other mechanisms of PDL1-mediated Th1 inhibition such as the conversion of Th1 cells to a regulatory phenotype have not been well characterized. We hypothesized that PDL1 may cause Th1 cells to manifest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
328
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 401 publications
(344 citation statements)
references
References 50 publications
12
328
1
3
Order By: Relevance
“…A recent report showed that PD-1/PD-L1 signaling converts human T H 1 cells into Tregs in vitro and in vivo, thereby preventing human-into-mouse xenogeneic graft-vs.-host disease. Recipient of T H 1 cells plus T cells expressing PD-L1 had a reduced number of T-bet + T cells and an increased number of Foxp3 + T cells (43). In this connection, we also noted an increased frequency and also absolute number of Tregs in certainbut not all-lymphoid compartments in NOD mice treated with IL-7Rα antibody.…”
Section: Discussionsupporting
confidence: 58%
“…A recent report showed that PD-1/PD-L1 signaling converts human T H 1 cells into Tregs in vitro and in vivo, thereby preventing human-into-mouse xenogeneic graft-vs.-host disease. Recipient of T H 1 cells plus T cells expressing PD-L1 had a reduced number of T-bet + T cells and an increased number of Foxp3 + T cells (43). In this connection, we also noted an increased frequency and also absolute number of Tregs in certainbut not all-lymphoid compartments in NOD mice treated with IL-7Rα antibody.…”
Section: Discussionsupporting
confidence: 58%
“…This provides an additional mechanism of how PD-1 blockade could cause worsening GvHD mortality. Amarnath et al 19 showed that PD-L1 caused human Th1 cells to convert into T reg cells both in vitro and in vivo resulting in inhibition of GvHD. In this experiment, restoration of GvHD was achieved by blocking PD-1 or by pharmacological inhibition of SHP1/SHP2, which are signaling molecules downstream to PD-1 receptor.…”
mentioning
confidence: 99%
“…It is already known that the PD1/PDL1 pathway is involved in the con-version of Th1 cells to Tregs. [78] Figure 1 depicts possible mechanism of PD1-PDL1 induced tolerance at the FMI.…”
Section: Pd1/pdl1 Pathway and Feto-maternal Tolerancementioning
confidence: 99%
“…[78] The PD1/PDL1 pathway is also thought to maintain peripheral tolerance. [45] The role of this pathway is relevant in the context of feto-maternal tolerance, as PDL1 is expressed on the trophoblast cells of the placenta and PD1 is expressed on the maternal effector and Tregs.…”
Section: Pd1/pdl1 Pathway and Feto-maternal Tolerancementioning
confidence: 99%